Necrotizing enterocolitis: clinical characteristics and outcome of a cohort of 106 cases at a children’s hospital in North China (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Necrotizing enterocolitis (NEC) in neonates, especially in the preterm, is a life-threatening condition. This study aims to analyze the clinical profile of NEC to get an insight for better understanding and management.Method: This was a retrospective analysis of neonatal NEC during the six-year period from 2014 to 2019. The prevalence and time for the development of NEC, clinical profile (term and preterm, low birth weight, gender, breast and formula feeding, abdominal distension, vomiting, hematochezia, apnea, fever, altered mental status, blood transfusion, breast or formula-fed, intestinal perforation, Bell’s stage and time for the development of NEC) and maternal factors (gestational hypertension, diabetes, premature rupture of membranes PROM, intrauterine fetal distress, placenta previa) were analyzed. Features in preterm and term neonates were compared. Ethical approval was obtained.Result: There were 106 NEC (0.87% of 12,184 neonatal admissions), 62 (58.49%) male, 90 (84.91%) preterm, and 85 (80.19%) LBW. Overall, 88 (83.02%) were Bell’s stage II, and severe stage III was seen in eight (19.04%) out of 42 babies with formula feeding as compared to one (1.56%) out of 64 in breastfeeding. The median time for the development of NEC was 6 days of life. The yearly prevalence of NEC per thousand neonates admitted during 6-years increased from 2.90 in 2014 to 12.06 in 2019. Overall mortality was 14 (13.20%).Conclusion: The yearly incidence of NEC increased with a higher incidence in preterm, in low birth weight and formula-fed neonates.